2016
DOI: 10.1002/cbf.3195
|View full text |Cite
|
Sign up to set email alerts
|

Increased 4‐hydroxy‐2‐nonenal‐induced proteasome dysfunction is correlated with cardiac damage in streptozotocin‐injected rats with isoproterenol infusion

Abstract: Increase in 4-hydroxy-2-nonenal (4HNE) due to oxidative stress has been observed in a variety of cardiac diseases such as diabetic cardiomyopathy. 4HNE exerts a damaging effect in the myocardium by interfering with subcellular organelles like mitochondria by forming adducts. Therefore, we hypothesized that increased 4HNE adduct formation in the heart results in proteasome inactivation in isoproterenol (ISO)-infused type 1 diabetes mellitus (DM) rats. Eight-week-old male Sprague Dawley rats were injected with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In addition, the present results identified that the mRNA and protein expression of NOX2 and NOX4 were significantly increased following AB surgery. As a lipid peroxide formed by the lipid peroxidation reaction between ROS and biomacromolecules, 4-HNE exerts a destructive effect on cardiac tissue by interfering with adducts formed by organelles such as mitochondria (37). In the present study, the expression of 4-HNE was significantly increased in the vehicle + AB group.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, the present results identified that the mRNA and protein expression of NOX2 and NOX4 were significantly increased following AB surgery. As a lipid peroxide formed by the lipid peroxidation reaction between ROS and biomacromolecules, 4-HNE exerts a destructive effect on cardiac tissue by interfering with adducts formed by organelles such as mitochondria (37). In the present study, the expression of 4-HNE was significantly increased in the vehicle + AB group.…”
Section: Discussionsupporting
confidence: 50%
“…In particular, the upregulation in 4-HNE because of oxidative stress was detected in numerous cardiac pathologies (e.g., diabetic cardiomyopathy). 4-HNE damages the myocardium, interfering with mitochondria and making adducts [72]. Previously, we reported not only a decrease in oxidative stress both in the serum and in the liver [33], but also in inflammation both in the brain [26] and in the adipose tissue [34] of HFD fed rats supplemented with tart cherries.…”
Section: Discussionmentioning
confidence: 92%
“…The increase in 4-HNE due to oxidative stress has been observed in several cardiac diseases, for example, diabetic cardiomyopathy. 4-HNE damages the myocardium by interfering with mitochondria and forming adducts [52].…”
Section: Discussionmentioning
confidence: 99%